NON BANK SHARIA HOUSING DECISION SEGMENT: HALAL FRIENDLY ENVIRONMENTAL EFFECTS AS MODERATION - Erike Anggraeni; Khavid Normasyhuri; Tri Atmaja Pramudita Wisnu Kusuma; Siti Nurohmah (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
Introduction: The study conducted by researchers aimed to examine the correlation between pricing and digital marketing, as well as the impact of a halal-friendly atmosphere on the robustness of non-bank sharia-based property purchasing choices. Methods: The research methodology used in this study is quantitative, using the software SmartPLS 3.0. The collection of primary data was conducted by sampling respondents, namely non-bank sharia housing customers, via the purposive sampling method. A total of 500 samples were used for the study. The data was obtained via the use of Google Form, with the indicator assessment being conducted using a Likert Scale. Results: The study findings indicate a favorable correlation between pricing and digital marketing in connection to the decision-making process for purchasing non-bank sharia property. The establishment of a halal-compliant setting enhances the correlation between pricing and digital marketing in the context of consumer choices about non-bank sharia-compliant housing. Conclusion and suggestion:  The objective of this study is to identify market opportunities and offer guidance to sharia housing developers in developing innovative housing concepts that align with market demands. Additionally, the study aims to enhance developers' understanding of and ability to respond to the needs and preferences of buyers seeking a halal-friendly living environment.